ANALISIS PENILAIAN RISIKO KEBISINGAN MENGGUNAKAN CONCEPTUAL MODEL DAN NOISE MAPPING PADA STASIUN ENGINE ROMeylit - Satriardi; Puji, Ari Andriyas; Meylita, Anggreini (SURYA TEKNIKA, 2022)
PT. Surya Intisari Raya is a palm oil factory has a factory capacity of 46.5 tons/hour. The engine room station which is a power station using steam which functions to expand steam to produce mechanical energy to drive a generator on a turbine engine. In operation, the machine makes noise. Noise is the emergence of unwanted sound so that it can interfere and endanger hearing health. it is necessary to analyze and control the risk using a conceptual model and noise mapping at the engine room station at PT.SIR, Sei Lukut. Based on the measurement results, the noise level of the generator engine is 92.4 dB, turbine engine 97.7 dB, back pressure vessel (BPV) engine 101.3 dB and turbine engine and BPV engine operating simultaneously 102.1 dB. Noise control is carried out by means of internal adaptation and external adaptation